Correlation functions of the degenerate relativistic electron gas with high density - Vavrukh, M. V.; Dzikovskyi, D. V.; Solovyan, V. B.; Tyshko, N. L. (Publishing House of Lviv Polytechnic National University, 2016)
The two- and three-particle correlation functions of degenerate relativistic model of homogeneous electron gas with Coulomb interactions at T = 0K in the momentum-frequency presentation in the local field approximation are investigated. These functions are sufficient for a correct calculation of the equation of state for the electron-nuclear model with the densities that correspond to the degenerate dwarfs. Дослiджено i розраховано дво- i тричастинковi кореляцiйнi функцiї моделi виродженого релятивiстського однорiдного електронного газу з кулонiвськими взаємодiями при T = 0K в iмпульсно-частотному зображеннi у наближеннi локального поля. Цих функцiй достатньо для коректного розрахунку рiвняння стану електрон-ядерної моделi при густинах, що вiдповiдають виродженим карликам.
Кореляцiйнi функцiї виродженого релятивiстського електронного газу високої густини
Keywords: reference system approach; n-particle correlation functions; the local field correction function; базисний пiдхiд; n-частинковi кореляцiйнi функцiї; поправка на локальне поле